Engagement militant et politisation des mobilisations au sein des oppositions urbaines à Istanbul - Clémence Petit (EchoGéo)
The Istanbul Greater Municipality has been implementing for a few years numerous ‘urban renewal projects’ to change Istanbul into a modern and competitive city on the global scene. Reacting to the demolitions and evictions of entire neighbourhoods caused by these projects, some inhabitants and ‘urban professionals’ mobilize within new movements and neighbourdhood associations. Beyond the distance they usually show towards politics – a condition of legitimacy in the securitarian system introduced in Turkey after the 1980 coup d’etat - these urban movements are going through struggles for defining the place of the political in the mobilisation. From the sociological study of two neighbourdhood associations and two movements of « urban professionnals », this contribution analyses the work for defining the framing and the repertoire of contention peculiar to each movement. It reveals the role of urban professionals in the political requalification of the division of the urban oppositions between a strategy of « expert » action and a more political-oriented strategy. Nevertheless, the analysis highlights the dynamic and relative character – in terms of contexts and scales – of the appropriation strategies of local policies and of the politicization process of urban movements.